2020
DOI: 10.1021/acs.joc.0c01985
|View full text |Cite
|
Sign up to set email alerts
|

Organic Dye-Catalyzed Intermolecular Radical Coupling of α-Bromocarbonyls with Olefins: Photocatalytic Synthesis of 1,4-Ketocarbonyls Using Air as an Oxidant

Abstract: An organic dye-catalyzed visible light-promoted ketocarbonylation protocol of vinyl arenes has been disclosed with the help of α-bromocarbonyls where aerial oxygen played a role of an oxidant to install the keto-oxygen functionality. This unique process is compatible with both internal and terminal olefins and tolerates a diverse array of functional groups (ketone, ester, amide, diketones, ketoester, and malonate). This process is mild and environmentally friendly and deals with greener oxidants like oxygen, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…Considering our interest in radical difunctionalization of olefins, 15 we disclose here the successful tackling of the above issues, allowing convenient access to various carboamination products from alkenes and neutral alkyl halides in nitrile solvent using 4CzIPN as an organic photocatalyst (Scheme 1C). We introduced zinc acetate as a multifunctional promoter which alters the traditional reaction course, enabling superior productivity to the existing method.…”
mentioning
confidence: 99%
“…Considering our interest in radical difunctionalization of olefins, 15 we disclose here the successful tackling of the above issues, allowing convenient access to various carboamination products from alkenes and neutral alkyl halides in nitrile solvent using 4CzIPN as an organic photocatalyst (Scheme 1C). We introduced zinc acetate as a multifunctional promoter which alters the traditional reaction course, enabling superior productivity to the existing method.…”
mentioning
confidence: 99%
“…Encouraged by the above results, a range of alkyl bromides were studied for further examination of the substrate scope ,, (Scheme ). The alkyl bromides with different substituents, such as methyl, benzyl, or ethyl groups, all could be used in the transformation smoothly, giving the desired products 4a – 4h in good yields (30–74%).…”
Section: Resultsmentioning
confidence: 99%
“…Such a result suggested that the reaction did not proceed in a ring-opening manner under the photoredox conditions. When the model reaction was performed under air, the oxidized product 6 could be detected by GC-MS (Scheme b), mechanistically implicating a benzylic radical intermediate . Further mechanistic investigations revealed that the addition of TEMPO (2,2,6,6-tetramethylpiperidinooxy) as a typical radical scavenger entirely abolished the desired multicomponent reaction, while the formation of radical trapping products 7 and 8 could be observed (Scheme c).…”
mentioning
confidence: 85%
“…When the model reaction was performed under air, the oxidized product 6 could be detected by GC-MS (Scheme 4b), mechanistically implicating a benzylic radical intermediate. 16 Further mechanistic investigations revealed that the addition of TEMPO (2,2,6,6-tetramethylpiperidinooxy) as a typical radical scavenger entirely abolished the desired multicomponent reaction, while the formation of radical trapping products 7 and 8 could be observed (Scheme 4c). We further explored whether the diarylamine underwent a nucleophilic addition reaction for C−N bond formation or a free radical crosscoupling process.…”
mentioning
confidence: 99%